Dracula - Francis, Ford Coppola, 1939-; Hopkins, Anthony; Keanu Reeves; Richard E GrantCary ElwesBill Campbell; Winona Ryder; Gary Oldman (USA American Zoetrope, 1992)
This version of Dracula is closely based on Bram Stoker's classic novel of the same name. A young lawyer (Jonathan Harker) is assigned to a gloomy village in the mists of eastern Europe. He is captured and imprisoned by the undead vampire Dracula, who travels to London, inspired by a photograph of Harker's betrothed, Mina Murray. In Britain, Dracula begins a reign of seduction and terror, draining the life from Mina's closest friend, Lucy Westenra. Lucy's friends gather together to try to drive Dracula away.
The vampire comes to England to seduce a visitor's fiance and inflict havoc in the foreign land.
Bram Stoker
Language: English
Subtitles: No subtitle
Keywords: Fantasy; Horror; Romance; Thriller; Drama